Annual plant reviews : Volume 43 : Biology of plant metabolomics - Hall, Robert D. (Robert David), 1958-; Wiley InterScience (Online service) (Chichester ; Ames, Iowa : Wiley-Blackwell, 2011)
Following a general introduction to the book, the first section of the book will include details of metabolomics of model species, including Arabidopsis, tomato and the legume Medicago. Chapters within the second section will consider the use and inter relationships of data integration, systems biology, genetics, genomics, metabolomics, chemometrics and biostatisitcs. The final section of the book will look at the use of metabolomics in food science, plant ecology, biodiversity and bioprocessing. Plant Metabolomics is an essential purchase for plant scientists, plant geneticists and physiologists.
Plant Metabolomics in a Nutshell: Potential and Future Challenges / Robert D Hall -- Metabolite Analysis and Metabolomics in the Study of Biotrophic Interactions between Plants and Microbes / John Draper, Susanne Rasmussen, Hassan Zubair -- Abiotic Stress and Metabolomics / Jairus Bowne, Antony Bacic, Mark Tester, Ute Roessner -- A Role for Metabolomics in Plant Ecology / Nicole M van Dam, Eddy van der Meijden -- Metabolomics of a Model Fruit: Tomato / Ric C H de Vos, Robert D Hall, Annick Moing -- Metabolomics of / Michael H Beale, Michael R Sussman -- Crops and Tasty, Nutritious Food -- How Can Metabolomics Help? / Derek Stewart, Louise V T Shepherd, Robert D Hall, Paul D Fraser -- Genetics, Genomics and Metabolomics / Alisdair R Fernie, Joost J B Keurentjes -- Data Integration, Metabolic Networks and Systems Biology / Henning Redestig, Jedrzej Szymanski, Masami Y Hirai, Joachim Selbig, Lothar Willmitzer, Zoran Nikoloski, Kazuki Saito -- Progress in Chemometrics and Biostatistics for Plant Applications, or: A Good Red Wine is a Bad White Wine / Joachim Kopka, Dirk Walther, J William Allwood, Royston Goodacre -- Spatially Resolved Plant Metabolomics / Lloyd W Sumner, Dong Sik Yang, Bennie J Bench, Bonnie S Watson, Chao Li, A Daniel Jones -- Data Processing, Metabolomic Databases and Pathway Analysis / Oliver Fiehn, Tobias Kind, Dinesh Kumar Barupal.
Includes bibliographical references and index.
Print version record.
Keywords: Plants -- Metabolism; Plants -- Metabolism; Electronic books